E-Dinar: Are they ready? - Mohd Nazri Muhayiddin; Elsadiq M.A.; Hishamuddin Ismail; Che Rusuli M. S. (Medwell Journals, 2017)
It is common for people to ask if they own gold or dinar, how can they use it to buy goods or services? The intention of this research is to address this issue by introducing a new concept of a payment system using electronic gold dinar (e-dinar). It is foreseen that if people can keep their money in a form of gold rather than in paper money, they would be able to buy goods or services with greater appreciating value. But before the actual system can be implemented, this research seeks to find out whether or not the public would be ready to adopt this concept of an electronic dinar payment system. The research framework is based on Unified Theory of Acceptance and Use of Technology (UTAUT). It measures the user acceptance based on these constructs; performance expectancy, effort expectancy, social influence, facilitating conditions, behavioral intention to use. In addition, attitude toward using, anxiety and perceived credibility are added as three new constructs. Furthermore, this research intends to investigate whether the moderating variables (e.g., age, gender, and experience) would have an effect on variables used in this study. Data collection is based on a questionnaire survey. A total of 872 samples were accepted for the purpose of this study. Structural Equation Modelling (SEM) is used to analyse the data. The results would be useful for the Malaysian government, local banks, institutions which offer electronic payment services wholesalers, retailers and most importantly the ordinary consumers.